2021
DOI: 10.1016/j.pharma.2021.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 outbreak on the reporting of adverse drug reactions associated with self-medication

Abstract: Objectives: The primary objective of the present study was to describe the characteristics of adverse drug reactions (ADRs) linked to self-medication that were notified to the French Pharmacovigilance Database (FPVD) during the COVID-19 outbreak in 2020 first wave. The secondary objective was to compare the characteristics of these ADRs in 2020 with those notified during the same calendar period a year previously Material and methods: We analyzed ADRs recorded in the FPVD between March 15th and May … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 14 publications
3
19
0
2
Order By: Relevance
“…The use of antibiotics during hospitalization could be explained by the confusion of a negative test in a patient with pneumonia, considering that the majority of the test made were serological rapid test with a limited value in diagnosis of acute COVID-19 infection. In addition, self-medication rates before admission to the hospital, a demonstrated harmful practice [14,51,52] were very high in our study (28.9%), being corticosteroids and antibiotics the most frequently self-administered.…”
Section: Plos Onementioning
confidence: 48%
“…The use of antibiotics during hospitalization could be explained by the confusion of a negative test in a patient with pneumonia, considering that the majority of the test made were serological rapid test with a limited value in diagnosis of acute COVID-19 infection. In addition, self-medication rates before admission to the hospital, a demonstrated harmful practice [14,51,52] were very high in our study (28.9%), being corticosteroids and antibiotics the most frequently self-administered.…”
Section: Plos Onementioning
confidence: 48%
“…This review reported the frequencies of self-medication with antibiotics from selected studies in the EMR countries (between 20% to 45%) and showed some patterns of SMA could be deduced. Self-medication to prevent or treat COVID-19 has become quite common among the public [ 33 , 34 , 35 ]. The rapid transmission and severity of COVID-19 disease sparked fear and stress among people worldwide due to the lack of definitive treatment and the disease’s elusive nature.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the significance of the self-medication impact of COVID-19 in any region can have an influence on the prevalence of such problems. Generally, the SMA was reported in several studies around the world including in developed and developing countries [ 33 , 34 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Demonstrating a higher proportion of medication errors in the COVID-19 period. 18 In addition, several studies have demonstrated a high prevalence of self-medication during the pandemic; Acharya et al . found a prevalence of 50.4% of self-medication among medical students and staff of a tertiary care center.…”
Section: Introductionmentioning
confidence: 99%